The Archaeology of Ethnogenesis : Race and Sexuality in Colonial San Francisco - Voss, Barbara L., 1967- (Book collections on Project MUSE., 2015)
This pioneering work of historical archaeology sheds light on the genesis of the Californios, a community of military settlers who forged a new identity on the northwest edge of Spanish North America. The revised edition includes a new preface from the author, looking at the development of ethnogenesis theory since the first edition of this book.